Preparation method of aluminum-based copper-clad plate, aluminum-based copper-clad plate and IGBT (Insulated Gate Bipolar Translator) module
By forming an oxide film layer, a silicon carbide layer and a nickel-copper alloy layer on an aluminum-based copper clad plate, the problems of poor thermal conductivity of ceramic substrates and difficulty in etching the etching lines are solved, and the high thermal conductivity and high voltage resistance are improved, and the simplification of the simplification of the performance of high thermal conductivity and high voltage resistance is achieved. The process and reduce costs.
Patent Information
- Application Number
- CN202411026566.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2025-01-03
AI Technical Summary
As the packaging substrate, the ceramic substrate has a poor thermal conductivity problem, and the etching lines between copper and ceramics are difficult to etch due to the use of titanium metal as an excessive layer.
The preparation method of aluminum-based copper clad plate includes forming an oxide film layer, a silicon carbide layer, a nickel-copper alloy layer and a first copper layer on the aluminum sheet to improve thermal conductivity and adhesion, solve the problem of difficulty in etching the etching line, and dissipate heat Parts and thermally conductive silicone enhance heat dissipation.
Significantly improves the thermal conductivity and thermal stability of aluminum-based copper clad plates, enhances the insulation and high voltage resistance of the surface, achieves better thermal expansion performance and adhesion, and the use of alternative ceramic substrates simplifies the process and reduces costs. .
Smart Images

Figure CN119252739A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of packaging carrier boards, in particular to a method for preparing an aluminum-based copper-clad laminate, an aluminum-based copper-clad laminate and an IGBT module. Background Art
[0002] The demand for high-power semiconductor packaging applications is increasing with the demand for new energy. The market demand for ceramic substrates with high temperature resistance and good insulation performance as packaging substrates is also increasing. For example, they are used as packaging substrates in high-power device IGBT (Insulated Gate Bipolar Transistor) modules.
[0003] Ceramic substrates have poor thermal conductivity as packaging substrates, and the etching circuits between copper and ceramics are difficult to etch because titanium metal is used as a transition layer. Summary of the invention
[0004] The embodiments of the present invention provide an aluminum-based copper-clad laminate preparation method, an aluminum-based copper-clad laminate and an IGBT module to solve the problem in the prior art that a ceramic substrate used as a packaging substrate has poor thermal conductivity and etching circuits are difficult to etch due to the use of titanium metal as a transition layer between copper and ceramic.
[0005] The invention discloses an IGBT module, comprising a housing, an IGBT chip and an aluminum-based copper-clad laminate; the aluminum-based copper-clad laminate comprises an aluminum plate, an oxide film layer, a silicon carbide layer, a nickel-copper alloy layer and a first copper layer; the oxide film layer is formed on both sides of the aluminum plate, the silicon carbide layer is formed on the oxide film layer on both sides of the aluminum plate, the nickel-copper alloy layer is formed on the silicon carbide layer on both sides of the aluminum plate, and the first copper layer is formed on the nickel-copper alloy layer on both sides of the aluminum plate;
[0006] The IGBT chip is fixed on the first copper layer of the aluminum-based copper-clad plate, and the shell is fixed on the aluminum-based copper-clad plate and covers the IGBT chip.
[0007] Optionally, a second copper layer and a first solder layer are arranged between the IGBT chip and the first copper layer, the second copper layer is fixed on the first copper layer, the first solder layer is fixed on the second copper layer, and the IGBT chip is fixed on the first solder layer.
[0008] Optionally, the IGBT module further includes a heat sink, which is fixedly arranged on a side of the aluminum-based copper-clad laminate facing away from the housing.
[0009] Optionally, the heat sink is made of aluminum, and a plurality of rows of heat sink fins are arranged on a side of the heat sink facing away from the aluminum-based copper-clad laminate.
[0010] Optionally, the heat sink is fixed on the aluminum-based copper-clad laminate by fasteners.
[0011] Optionally, thermal conductive silicone is coated between the heat sink and the aluminum-based copper-clad laminate.
[0012] Optionally, the interior of the shell is filled with organic silicon material, and the organic silicon material encapsulates and fixes the IGBT chip.
[0013] Optionally, the interior of the shell is filled with epoxy resin, and the epoxy resin is filled between the silicone material and the top of the shell.
[0014] Optionally, the thickness of the oxide film layer is 12 um to 25 um; and / or the thickness of the silicon carbide layer is 500 nm to 5000 nm.
[0015] Optionally, the thickness of the nickel-copper alloy layer is 70 nm to 100 nm; and / or the thickness of the first copper layer is 0.2 mm to 0.5 mm.
[0016] Compared with the prior art, the aluminum-based copper-clad laminate provided by the embodiment of the present invention has the following beneficial effects: the aluminum-based copper-clad laminate prepared by the preparation method of the present invention can greatly improve the thermal conductivity, and the surface coefficient of thermal expansion (CTE) of the aluminum-based copper-clad laminate is small, the thermal expansion performance is good, and the thermal stability is better; and the adhesion between the layers of the aluminum-based copper-clad laminate is better, and the surface insulation and high voltage resistance performance are excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments, in which:
[0018] Figure 1 It is a schematic diagram of the traditional IGBT module packaging structure;
[0019] Figure 2 is a schematic diagram of an IGBT module according to an embodiment of the present invention;
[0020] Figure 3 Schematic diagram of an aluminum-based copper-clad laminate according to an embodiment of the present invention.
[0021] The reference numerals in the figures are:
[0022] 1. Shell; 2. IGBT chip; 3. Aluminum-based copper-clad laminate; 31. Aluminum plate; 32. Oxide film layer; 33. Silicon carbide layer; 34. Nickel-copper alloy layer; 35. First copper layer; 4. Second copper layer; 5. First solder layer; 6. Heat sink; 61. Heat sink fins; 7. Fasteners; 8. Thermally conductive silicone; 9. Silicone material; 10. Epoxy resin; 20. Metal bonding wire; 30. Busbar terminal; 40. Copper layer; 50. Solder layer; 60. Ceramic substrate; 70. Copper thermal block. DETAILED DESCRIPTION
[0023] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. Now, in conjunction with the accompanying drawings, a preferred embodiment of the present invention is described in detail.
[0024] The embodiment of the present invention provides an aluminum-based copper-clad laminate 3, such as Figure 3 As shown, the method for preparing the aluminum-based copper-clad laminate 3 includes the following steps:
[0025] S100: Use acid solution to clean the surface oxides on both sides of the aluminum plate;
[0026] S200: Corona treatment of both sides of the aluminum plate after cleaning with an acid solution, forming an oxide film layer on both sides of the aluminum plate;
[0027] S300: A silicon carbide layer is plated on the oxide film layer on both sides of the aluminum plate;
[0028] S400: A nickel-copper alloy layer is plated on the silicon carbide layer on one side;
[0029] S500: A first copper layer is plated on the nickel-copper alloy layer to obtain an aluminum-based copper-clad laminate.
[0030] The aluminum-based copper-clad laminate 3 prepared by the preparation method of the present invention can greatly improve the thermal conductivity, and the surface thermal expansion coefficient (CTE) of the aluminum-based copper-clad laminate 3 is small, the thermal expansion performance is good, and the thermal stability is better; and the adhesion between the layers of the aluminum-based copper-clad laminate 3 is better, and the surface insulation and high voltage resistance performance are excellent.
[0031] Specifically, in the aluminum-based copper-clad laminate 3 of the present invention, the thermal conductivity of the silicon carbide layer 33 can reach up to 400W / mK, which increases the infrared emissivity of the aluminum-based copper-clad laminate 3 and improves the overall heat dissipation effect of the aluminum-based copper-clad laminate 3. Therefore, plating the silicon carbide layer 33 on the aluminum plate 31 can improve the thermal conductivity of the aluminum-based copper-clad laminate 3; the CTE value of the aluminum plate 31 itself is very large, which is 26 times that of ceramics. Plating the silicon carbide layer 33 on the aluminum plate 31 can reduce the CTE value.
[0032] The aluminum plate 31 itself has a relatively soft structure and low structural strength, and it is difficult to firmly bond with the silicon carbide layer 33, so the silicon carbide layer 33 and the aluminum plate 31 are easily delaminated, and the oxide film layer 32 can increase the adhesion between the silicon carbide layer 33 and the aluminum plate 31, improve the adhesion of the silicon carbide layer 33, and increase the content of the silicon carbide layer 33. The aluminum plate 31 itself is not insulating. The present invention first forms an oxide film layer 32 on the surface of the aluminum plate 31 and then plates the silicon carbide layer 33, which can improve the insulation of the aluminum-based copper clad plate 3. That is, the silicon carbide layer 33 can enhance the surface hardness of the aluminum plate 31 and improve the impact resistance, and can also make the aluminum plate 31 insulating.
[0033] The nickel-copper alloy layer 34 is used as a transition layer between the silicon carbide layer 33 and the first copper layer 35, which can solve the problem that the pure copper material is too soft to form a good adhesion with the silicon carbide layer 33, and at the same time solve the problem that the etching circuit between the copper and the ceramic in the ceramic substrate 60 is difficult to etch due to the use of titanium metal as a transition layer.
[0034] Therefore, the aluminum-based copper-clad laminate 3 of the present invention forms an oxide film layer 32 on the surface of the aluminum plate 31, and the surface is plated with a silicon carbide layer 33 to solve the insulation and voltage resistance problems. The voltage resistance after treatment can reach more than 2000 volts, and after the silicon carbide layer 33 is plated, the voltage resistance can be increased to more than 7000 volts. The thermal conductivity of the aluminum-based copper-clad laminate 3 can reach 280W / mK, which is more than 8 times that of the current alumina ceramic substrate 60.
[0035] Specifically, the aluminum plate 31 can be a pure aluminum plate 31 or an aluminum alloy plate. When the aluminum-based copper-clad laminate 3 is used as a packaging substrate, the first copper layer 35 is used as a conductor to conduct electricity. The aluminum-based copper-clad laminate 3 of the present invention can be used to replace the existing ceramic substrate 60, and can also be used in products with high thermal conductivity and heat dissipation requirements.
[0036] Specifically, the step of cleaning the surface oxides of the aluminum plate with an acid solution is as follows: cleaning the surface oxides of the aluminum plate with dilute sulfuric acid at a concentration of 2% to 5%. Aluminum easily reacts with oxygen in the air to generate aluminum oxide, forming a layer of oxide. The use of dilute sulfuric acid can effectively remove these oxides, ensure the surface of the aluminum plate 31 is clean, and provide a good substrate for subsequent corona treatment and coating. During the pickling process, dilute sulfuric acid not only removes oxides, but also may cause micro-etching on the aluminum surface, increasing the surface roughness. This roughness helps to improve the adhesion of the subsequent coating to the aluminum substrate. The use of dilute sulfuric acid at a concentration of 2% to 5% can effectively remove oxides, while avoiding excessive corrosion and increased costs that may be caused by excessive concentrations. Specifically, the concentration of dilute sulfuric acid can be any of 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, and 5%.
[0037] The step of forming an oxide film layer on the surface of the aluminum plate after cleaning with the corona acid solution is specifically as follows: forming an oxide film layer with a thickness of 12um to 25um on the surface of the aluminum plate after cleaning with the corona acid solution. The oxide film layer 32 serves as a medium between the aluminum plate 31 and the subsequent coating, and its existence significantly improves the adhesion between the layers. The thickness of the oxide film layer 32 is between 12um and 25um, which provides sufficient mechanical anchor points for the coating and helps to improve the stability of the overall structure. The thermal expansion coefficient (CTE) of aluminum is large, while the CTE of aluminum oxide is relatively small. By forming an oxide film layer 32 of a certain thickness, the CTE of the aluminum-based copper clad laminate 3 can be reduced to a certain extent, and its thermal stability can be improved. Although the thermal conductivity of aluminum oxide is lower than that of metals such as copper, by controlling the thickness of the oxide film layer 32, the overall thermal conductivity can be improved by subsequent high thermal conductivity materials such as silicon carbide layer 33 while maintaining good insulation performance. The thickness range of the oxide film layer 3212um to 25um provides flexibility, and the thickness of the oxide film layer 32 can be adjusted according to different application needs and performance requirements to achieve the best performance balance. Specifically, the thickness of the oxide film layer 32 can be any one of 12um, 14um, 16um, 18um, 20um, 22um, and 24um.
[0038] Specifically, in step S200, the aluminum plate cleaned with the acid solution is subjected to electrode bombardment on the surface of the aluminum plate using a corona device to form an oxide film layer with a thickness of 12 um to 25 um.
[0039] In step S300, a magnetron physical vapor deposition device (PVD) is used, the target material is 99.9% pure silicon carbide, and a 500nm to 5000nm silicon carbide layer is plated on the oxide film layer. Specifically, the thickness of the silicon carbide layer 33 can be any one of 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1000nm, 1500nm, 2000nm, 2500nm, 3000nm, 4000nm, and 5000nm.
[0040] In step S400, after the aluminum plate is plated with the silicon carbide layer, it is transferred to another PVD device, the target material is a nickel-copper alloy (alloy ratio is nickel: copper = 7:3), and a nickel-copper alloy layer is plated on the silicon carbide layer, and the thickness of the nickel-copper alloy layer is 70nm to 100nm. Specifically, the thickness of the nickel-copper alloy layer 34 can be any one of 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, and 100nm.
[0041] Specifically, step S500 of plating the first copper layer on the nickel-copper alloy is as follows: sputtering a first copper layer with a thickness of 1000nm to 2000nm on the nickel-copper alloy, and then electroplating the first copper layer with a thickness of 1000nm to 2000nm to a thickness of 0.2mm to 0.5mm. Sputtering is a physical vapor deposition technology that can form a uniform thin film. Sputtering has high cost and low efficiency, while electroplating can further increase the thickness of the first copper layer 35 to ensure the uniformity and integrity of the first copper layer 35. The bonding force between the sputtered first copper layer 35 and the nickel-copper alloy layer 34 is strong, while electroplating the first copper layer 35 can further enhance the bonding force and improve the stability of the overall structure. By combining sputtering and electroplating, material usage and production costs can be optimized while ensuring performance. Therefore, in this solution, a first copper layer 35 with a thickness of 1000nm to 2000nm is sputtered, and then the first copper layer 35 with a thickness of 1000nm to 2000nm is electroplated to a thickness of 0.2mm to 0.5mm, so as to improve efficiency and reduce cost.
[0042] Specifically, the thickness of the sputtered first copper layer 35 can be any one of 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1600nm, 1700nm, 1800nm, 1900nm, and 2000nm. Specifically, a first copper layer 35 with a thickness of 1000nm to 2000nm is sputtered on a nickel-copper alloy by vacuum nano-plating technology, and then the first copper layer 35 with a thickness of 1000nm to 2000nm is electroplated to a thickness of 0.2mm to 0.5mm by a vertical copper plating line (VCP). Vacuum nano-plating is a surface treatment technology that deposits materials (such as copper) on a substrate material in nanoscale particles under a vacuum environment. The vertical copper plating line is an electroplating device used in the manufacture of electronic packaging materials, which allows the material to be suspended vertically in an electroplating tank and deposits the first copper layer 35 on the surface of the material by electroplating. VCP technology can provide a uniform coating and can control the thickness of the coating.
[0043] Furthermore, after the step of plating the first copper layer 35 on the nickel-copper alloy layer 34 , the first copper layer 35 is subjected to an anti-oxidation treatment, namely, a corona treatment.
[0044] like Figure 3 As shown, the present invention also discloses an aluminum-based copper-clad laminate 3, comprising an aluminum plate 31, an oxide film layer 32, a silicon carbide layer 33, a nickel-copper alloy layer 34 and a first copper layer 35; the oxide film layer 32 is formed on both sides of the aluminum plate 31, the silicon carbide layer 33 is formed on the oxide film layer 32 on both sides of the aluminum plate 31, the nickel-copper alloy layer 34 is formed on the silicon carbide layer 33 on both sides of the aluminum plate 31, and the first copper layer 35 is formed on the nickel-copper alloy layer 34 on both sides of the aluminum plate 31.
[0045] The aluminum-based copper-clad laminate 3 of the present invention can greatly improve thermal conductivity, and the surface coefficient of thermal expansion (CTE) of the aluminum-based copper-clad laminate 3 is small, the thermal expansion performance is good, and the thermal stability is better; and the adhesion between the layers of the aluminum-based copper-clad laminate 3 is better, and the surface insulation and high voltage resistance performance are excellent.
[0046] Specifically, in the aluminum-based copper-clad laminate 3 of the present invention, the thermal conductivity of the silicon carbide layer 33 can reach up to 400W / mK, which increases the infrared emissivity of the aluminum-based copper-clad laminate 3 and improves the overall heat dissipation effect of the aluminum-based copper-clad laminate 3. Therefore, plating the silicon carbide layer 33 on the aluminum plate 31 can improve the thermal conductivity of the aluminum-based copper-clad laminate 3; the CTE value of the aluminum plate 31 itself is very large, which is 26 times that of ceramics. Plating the silicon carbide layer 33 on the aluminum plate 31 can reduce the CTE value.
[0047] The aluminum plate 31 itself has a relatively soft structure and low structural strength, and it is difficult to firmly bond with the silicon carbide layer 33, so the silicon carbide layer 33 and the aluminum plate 31 are easily delaminated, and the oxide film layer 32 can increase the adhesion between the silicon carbide layer 33 and the aluminum plate 31, improve the adhesion of the silicon carbide layer 33, and increase the content of the silicon carbide layer 33. The aluminum plate 31 itself is not insulating. The present invention first forms an oxide film layer 32 on the surface of the aluminum plate 31 and then plates the silicon carbide layer 33, which can improve the insulation of the aluminum-based copper clad plate 3. That is, the silicon carbide layer 33 can enhance the surface hardness of the aluminum plate 31 and improve the impact resistance, and can also make the aluminum plate 31 insulating.
[0048] The nickel-copper alloy layer 34 is used as a transition layer between the silicon carbide layer 33 and the first copper layer 35, which can solve the problem that the pure copper material is too soft to form a good adhesion with the silicon carbide layer 33, and at the same time solve the problem that the etching circuit between the copper and the ceramic in the ceramic substrate 60 is difficult to etch due to the use of titanium metal as a transition layer.
[0049] Therefore, the aluminum-based copper-clad laminate 3 of the present invention forms an oxide film layer 32 on the surface of the aluminum plate 31, and the surface is plated with a silicon carbide layer 33 to solve the insulation and voltage resistance problems. The voltage resistance after treatment can reach more than 2000 volts, and after the silicon carbide layer 33 is plated, the voltage resistance can be increased to more than 7000 volts. The thermal conductivity of the aluminum-based copper-clad laminate 3 can reach 280W / mK, which is more than 8 times that of the current alumina ceramic substrate 60.
[0050] Specifically, the thickness of the oxide film layer 32 is 12um to 25um. In this solution, the thickness of the oxide film layer 32 is between 12um and 25um, which provides sufficient mechanical anchor points for the coating and helps to improve the stability of the overall structure. The coefficient of thermal expansion (CTE) of aluminum is large, while the CTE of aluminum oxide is relatively small. By forming an oxide film layer 32 of a certain thickness, the CTE of the aluminum-based copper clad laminate 3 can be reduced to a certain extent and its thermal stability can be improved. Specifically, the thickness of the oxide film layer 32 can be any one of 12um, 14um, 16um, 18um, 20um, 22um, and 24um.
[0051] Specifically, the thickness of the silicon carbide layer 33 is 500nm to 5000nm. In this solution, the silicon carbide layer 33 has a high thermal conductivity. This thickness range can ensure that the aluminum-based copper-clad laminate 3 has good heat dissipation performance, which helps to quickly transfer heat from the heating element and dissipate it outward. The thermal expansion coefficient of the silicon carbide layer 33 is lower than that of aluminum. By controlling the thickness of the silicon carbide layer 33, the overall thermal expansion of the aluminum-based copper-clad laminate 3 can be adjusted to a certain extent to match the thermal expansion characteristics of other electronic components when it is used. Specifically, the thickness of the silicon carbide layer 33 can be any one of 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, and 1000nm.
[0052] Specifically, the thickness of the nickel-copper alloy layer 34 is 70nm to 100nm. In this solution, the nickel-copper alloy layer 34 serves as an intermediate transition layer, and its appropriate thickness helps to improve the bonding force between the silicon carbide layer 33 and the first copper layer 35, thereby enhancing the stability of the overall structure. By controlling the thickness of the nickel-copper alloy layer 34, the thermal expansion coefficient of the entire aluminum-based copper-clad laminate 3 can be further adjusted to adapt to different application environments. Specifically, the thickness of the nickel-copper alloy layer 34 can be any one of 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, and 100nm.
[0053] Specifically, the thickness of the first copper layer 35 is 0.2 mm to 0.5 mm. In this solution, the increase in the thickness of the first copper layer 35 can significantly improve the electrical conductivity of the material, which is particularly important for electronic packaging materials. Copper also has good thermal conductivity, and a thicker first copper layer 35 helps to more effectively conduct heat from the electronic components to the substrate and dissipate it, thereby improving the overall heat dissipation efficiency.
[0054] Specifically, the aluminum plate 31 may be a pure aluminum plate or an aluminum alloy plate.
[0055] like Figures 1 to 3As shown, the present invention also discloses an IGBT module, including the aluminum-based copper-clad laminate 3 prepared by the above preparation method, or the above aluminum-based copper-clad laminate 3; the aluminum-based copper-clad laminate 3 is used as a packaging carrier of the IGBT module. Since the IGBT module of the present invention has the above aluminum-based copper-clad laminate 3 or the aluminum-based copper-clad laminate 3 prepared by the above preparation method, it also has the specific structure and technical effects of the above aluminum-based copper-clad laminate 3 or the aluminum-based copper-clad laminate 3 prepared by the above preparation method, which will not be repeated here.
[0056] Furthermore, the IGBT module also includes a housing 1, an IGBT chip 2 and an aluminum-based copper-clad laminate 3; the IGBT chip 2 is fixed on the first copper layer 35 of the aluminum-based copper-clad laminate 3, and the housing 1 is fixed on the aluminum-based copper-clad laminate 3 and covers the IGBT chip 2. The IGBT module in the present invention uses the aluminum-based copper-clad laminate 3 as a package carrier, the IGBT chip 2 is fixed on the first copper layer 35 of the aluminum-based copper-clad laminate 3, does not use a ceramic substrate 60 and a copper heat-conducting block 70, and eliminates the copper layer 40 and the solder layer 50 between the ceramic substrate 60 and the copper heat-conducting block 70, saves the ceramic substrate 60, the copper heat-conducting block 70 and the bonding process cost, has low cost, simple process, improves production yield, has a simpler and singler structure, eliminates the heat conduction resistance caused by the multi-layer structure, and has high heat conduction efficiency.
[0057] Specifically, a second copper layer 4 and a first solder layer 5 are arranged between the IGBT chip 2 and the first copper layer 35, the second copper layer 4 is fixed on the first copper layer 35, the first solder layer 5 is fixed on the second copper layer 4, and the IGBT chip 2 is fixed on the first solder layer 5. The first solder layer 5 firmly fixes the IGBT chip 2 on the second copper layer 4 during the welding process. The first solder layer 5 has good ductility and toughness under thermal cycles and mechanical stress, which helps to improve the reliability of the module. The IGBT module also includes a busbar terminal 30, the IGBT chip 2 is electrically connected to the busbar terminal 30, and is electrically connected to the outside of the housing 1 through the busbar terminal 30. Specifically, as Figure 2 As shown, each electrode (such as the emitter, collector and gate) of the IGBT chip 2 uses a metal bonding wire 20, which is electrically connected to the second copper layer 4 through a wire bonding technology, and transmits current from the IGBT chip 2 to the external circuit through the busbar terminal 30, thereby achieving electrical connection with the external circuit. The metal bonding wire 20 can be a gold wire, an aluminum wire or a copper wire.
[0058] The IGBT module also includes a heat sink 6, which is fixed on the side of the aluminum-based copper-clad laminate 3 facing away from the housing 1. The provision of the heat sink 6 can significantly improve the heat dissipation capacity of the IGBT module. Since the IGBT module generates a large amount of heat when working, an effective heat dissipation design is essential to maintaining the stable operation and extending the service life of the IGBT module. Specifically, the heat sink 6 is made of aluminum, and a plurality of rows of heat sink fins 61 are provided on the side of the heat sink 6 facing away from the aluminum-based copper-clad laminate 3. The plurality of rows of heat sink fins 61 increase the surface area of the heat sink 6, thereby improving the heat dissipation efficiency and allowing more heat to be dissipated through air convection. The heat sink 6 is fixed on the aluminum-based copper-clad laminate 3 by fasteners 7. The use of fasteners 7 can ensure that a stable mechanical connection is formed between the heat sink 6 and the aluminum-based copper-clad laminate 3, reducing displacement or falling off due to vibration or thermal expansion. The fasteners 7 can be rivets, screws, etc.
[0059] Furthermore, a thermally conductive silicone 8 is coated between the heat sink 6 and the aluminum-based copper-clad laminate 3. As a thermally conductive material, the thermally conductive silicone 8 can effectively fill the micro gap between the heat sink 6 and the aluminum-based copper-clad laminate 3 to form a thin and uniform heat conduction layer, improve the thermal interface, reduce thermal resistance, and improve the efficiency of heat transfer from the IGBT chip 2 to the heat sink 6.
[0060] Furthermore, the interior of the shell is filled with silicone material 9, and the silicone material 9 encapsulates and fixes the IGBT chip 2. The filling of the silicone material 9 can provide a stable support for the IGBT chip 2 and reduce the displacement or damage caused by vibration or impact. The filled silicone material 9 can protect the IGBT chip 2 from moisture, dust and other environmental factors, and extend the service life of the IGBT chip 2. The interior of the shell is filled with epoxy resin 10, and the epoxy resin 10 is filled between the silicone material 9 and the top of the shell 1. The epoxy resin 10 has high mechanical strength and can provide additional physical protection for the IGBT chip 2 to resist external shocks and vibrations. The filling of the epoxy resin 10 can reduce the noise caused by vibration of the internal components of the IGBT module and improve the working stability of the module.
[0061] It should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. For those skilled in the art, the technical solutions described in the above embodiments can be modified, or some of the technical features therein can be replaced by equivalents; and all these modifications and replacements should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing an aluminum-based copper-clad laminate, characterized in that: Includes steps: Clean the surface oxides on both sides of the aluminum plate with an acid solution; After the corona treatment acid solution is cleaned, an oxide film layer is formed on both sides of the aluminum plate surface; A silicon carbide layer is plated on the oxide film layer on both sides of the aluminum plate; A nickel-copper alloy layer is plated on the silicon carbide layer on one side; A first copper layer is plated on the nickel-copper alloy layer to obtain an aluminum-based copper-clad laminate.
2. The preparation method according to claim 1, characterized in that: The step of plating the first copper layer on the nickel-copper alloy is specifically as follows: The step S500 of plating the first copper layer on the nickel-copper alloy is specifically: sputtering a first copper layer with a thickness of 1000nm to 2000nm on the nickel-copper alloy, and then electroplating the first copper layer with a thickness of 1000nm to 2000nm to a thickness of 0.2mm to 0.5mm.
3. The preparation method according to claim 1, characterized in that: The step of cleaning the surface oxide of the aluminum plate with an acid solution is specifically as follows: Use 2% to 5% concentration of dilute sulfuric acid to clean the surface oxides of the aluminum plate; The steps of forming an oxide film layer on the surface of the aluminum plate after being cleaned with the corona acid solution are specifically as follows: After being cleaned with the corona acid solution, an oxide film layer with a thickness of 12um to 25um is formed on the surface of the aluminum plate.
4. An aluminum-based copper-clad laminate, characterized in that: It includes an aluminum plate, an oxide film layer, a silicon carbide layer, a nickel-copper alloy layer and a first copper layer; the oxide film layer is formed on both sides of the aluminum plate, the silicon carbide layer is formed on the oxide film layer on both sides of the aluminum plate, the nickel-copper alloy layer is formed on the silicon carbide layer on both sides of the aluminum plate, and the first copper layer is formed on the nickel-copper alloy layer on both sides of the aluminum plate.
5. The aluminum-based copper-clad laminate according to claim 4, characterized in that: The thickness of the oxide film layer is 12um to 25um.
6. The aluminum-based copper-clad laminate according to claim 4, characterized in that: The thickness of the silicon carbide layer is 500nm-5000nm.
7. The aluminum-based copper-clad laminate according to claim 4, characterized in that: The thickness of the nickel-copper alloy layer is 70nm-100nm.
8. The aluminum-based copper-clad laminate according to claim 4, characterized in that: The thickness of the first copper layer is 0.2 mm to 0.5 mm.
9. The aluminum-based copper-clad laminate according to claim 4, characterized in that: The aluminum plate is a pure aluminum plate or an aluminum alloy plate.
10. An IGBT module, characterized in that: It comprises an aluminum-based copper-clad laminate prepared by the preparation method described in any one of claims 1 to 3, or an aluminum-based copper-clad laminate described in any one of claims 4 to 9; the aluminum-based copper-clad laminate is used as a packaging carrier for the IGBT module.
